2020
DOI: 10.1111/cpr.12797
|View full text |Cite
|
Sign up to set email alerts
|

H3K27ac‐activated LINC00519 promotes lung squamous cell carcinoma progression by targeting miR‐450b‐5p/miR‐515‐5p/YAP1 axis

Abstract: Objectives Long non‐coding RNAs (lncRNAs) are extensively reported as participants in the biological process of diverse malignancies, including lung squamous cell carcinoma (LUSC). Long intergenic non‐protein coding RNA 519 (LINC00519) is identified as a novel lncRNA which has not yet been studied in cancers. Materials and Methods LINC00519 expression was detected by qRT‐PCR. The effect of LINC00519 on LUSC cellular activities was determined by in vitro and in vivo assays. Subcellular fractionation and FISH as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…LINC00519 expression is upregulated in lung squamous cell carcinoma. 26 High LINC00519 expression is closely associated with an unsatisfactory prognosis in patients with lung squamous cell carcinoma. 26 Functionally, LINC00519 exerts pro-oncogenic roles in lung squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LINC00519 expression is upregulated in lung squamous cell carcinoma. 26 High LINC00519 expression is closely associated with an unsatisfactory prognosis in patients with lung squamous cell carcinoma. 26 Functionally, LINC00519 exerts pro-oncogenic roles in lung squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…26 High LINC00519 expression is closely associated with an unsatisfactory prognosis in patients with lung squamous cell carcinoma. 26 Functionally, LINC00519 exerts pro-oncogenic roles in lung squamous cell carcinoma cells. 26 In contrast, the expression profile and biological functions of LINC00519 in TSCC have rarely been documented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long intergenic non-protein-coding RNA 519 (LINC00519) was first described in lung squamous cell carcinoma (LUSC) as an oncogene [96]. Localization analysis indicated that the vast majority of these lincRNA molecules can be found in the cytoplasm where they act as an miRNA-sequestering sponge [97].…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 99%